PERANCANGAN SISTEM INVENTORI KARBON AKTIF BERDASARKAN METODE REORDER POINT BERBASIS WEB - Syukron Fajri Afiantanto; Atiqah Meutia Hilda (UHAMKA Press, 2022)
This study aims to design an application that makes it easy for users and users to process production inventory records that determine when to buy raw material inventory online and also aims to minimize loss or damage data in reporting the result of a complete and whole. Methods used in this research is in a rapid application development, because this method faster and systematic in order to facilitate in doing design system. The results obtained in the development of this system proved that the Design of an Activated Carbon Inventory System Based on the Web-Based Reorder Point Method at PT. Freeman has been successfully run or used to make it easier for operators to quickly and efficiently manage an inventory of activated carbon data online. Demonstrable satisfaction index of operators pt freeman worth 76,19 % indicating as good category